2011
DOI: 10.1097/sla.0b013e3182111195
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Improvement of Survival Outcomes of Resection of Hepatocellular Carcinoma

Abstract: A continuous improvement of survival outcomes after hepatectomy for HCC was achieved in the past 20 years even in patients with advanced diseases. Hepatectomy remains the treatment of choice for resectable HCC in a predominantly hepatitis B virus-based Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
244
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(268 citation statements)
references
References 24 publications
13
244
2
9
Order By: Relevance
“…As a result, patient survival significantly increased in the later era, which is a reflection of the various factors mentioned above. Other studies have also observed similar trends in survival 34, 37, 45, 46. Despite demonstrating a significant improvement of survival over time, the median survival of 18.6 months in the later era still seems rather low.…”
Section: Discussionsupporting
confidence: 58%
“…As a result, patient survival significantly increased in the later era, which is a reflection of the various factors mentioned above. Other studies have also observed similar trends in survival 34, 37, 45, 46. Despite demonstrating a significant improvement of survival over time, the median survival of 18.6 months in the later era still seems rather low.…”
Section: Discussionsupporting
confidence: 58%
“…Surgery, tumor ablation, and liver transplantation are the main potentially curative treatments for HCC. However, tumor recurrence rate is very high after liver resection and tumor ablation, which is a major problem affecting long term survival (4,5). Various postoperative interventions, such as adjuvant therapy with interferon, Vitamin E or K2, or I 131 , are used to reduce the incidence of tumor recurrence after curative treatment (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…20 This form of treatment should be reconsidered because over the last 20 years, there has been a continuous improvement in survival after HCC resection, even in older patients. 21 A tumor that is resectable must be present together with adequate functional liver reserve for sustaining life (found mostly in patients with Child-Pugh status A but sometimes in patients with Child-Pugh status B); this makes this treatment subset of elderly patients with HCC even smaller than the other subgroups. 22 There is evidence that this subgroup may be increasing in some countries.…”
Section: See Article On Page 423mentioning
confidence: 99%